Z-DNA-Binding Protein 1 Is Critical for Controlling Virus Replication and Survival in West Nile Virus Encephalitis - Rothan, Hussin A.; Arora, Komal; Natekar, Janhavi P.; Strate, Philip G.; Brinton, Margo A.; Kumar, Mukesh (Frontiers in Microbiology, 2019)
WWest Nile virus (WNV), a neurotropic flavivirus, is the leading cause of viral encephalitis in the United States. Recently, ZIKV infections have caused serious neurological diseases and birth defects, specifically Guillain-Barrè syndrome and microcephaly. Z-DNA binding protein 1 (ZBP1) is a cytoplasmic sensor that that has been shown to play a significant role in initiating a robust immune response. We previously reported that WNV and ZIKV infections induce dramatic up-regulation of ZBP1 in mouse brain as well as in infected primary mouse cells. Herein, we show the critical role of ZBP1 in restricting the pathogenesis of WNV and ZIKV infection. Deletion of ZBP1 resulted in significantly higher morbidity and mortality after infection with a pathogenic WNV NY99 strain in mice. No mortality was observed in wild-type (WT) mice infected with the non-pathogenic WNV Eg101 strain. Interestingly, infection of ZBP1-/- mice with WNV Eg101 was lethal resulting in 100% mortality, suggesting that ZBP1 is required for survival after WNV infection. Viremia and brain viral load were significantly higher in ZBP1-/- mice compared to WT mice. In addition, protein levels of interferon (IFN)-α, and inflammatory cytokines and chemokines were significantly higher in the serum and brains of ZBP1-/- mice compared to the WT mice. Primary mouse cortical neurons and mouse embryonic fibroblasts (MEFs) derived from ZBP1-/- mice produced higher virus titers compared to WT cells after infection with WNV NY99 and WNV Eg101. Similarly, neurons and MEFs lacking ZBP1 exhibited significantly enhanced replication of PRVABC59 (Asian) and MR766 (African) strains of ZIKV compared to WT cells. The knockout of ZBP1 function in MEFs inhibited ZBP1-dependent virus-induced cell death. In conclusion, these data reveal that ZBP1 restricts WNV and ZIKV production in mouse cells and is required for survival of a peripheral WNV infection in mice.